SATELLITE TRACKING OF GRAY SEALS (HALICHOERUS-GRYPUS) - MCCONNELL, B J; CHAMBERS, C; NICHOLAS, K S; FEDAK, M A (1992)
Three types of Argos satellite transmitter were attached to grey seals (Halichoerus grypus) at Donna Nook (South Humberside, UK) between 1985 and 1989 in order to investigate their movements. With the first two transmitters (A and B) the entire package was attached to the seal's back. Seal A was tracked for 29 days but although it was located on sandbanks up to 150 km south-east of Donna Nook, no locations were obtained at sea. Transmitters B and C used a submergence sensor to regulate transmissions. Seal B was tracked for 51 days and remained within 40 km of Donna Nook. A few locations were obtained at sea but all within 10 km of Donna Nook. Transmitter C incorporated a head-mounted aerial in order to increase the number of location fixes when the seal was at sea. This seal was tracked for 111 days, producing an average of 9.1 location fixes per day while at sea. It used two sites 265 km apart and undertook three transits between them. On the second visit to the northern site it made several trips up to 55 km out to sea. The majority of the remainder of the time was spent within 10 km of the haulout sites. Estimates of swimming speed were consistent with values required for minimum cost of transport.